ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI MOTIVASI KERJA KARYAWAN PADA PABRIK PENGOLAHAN MAKANAN INTI RASA SINGKAWANG - Atmojo, Singgih Tiwut; Irianta Denashurya, Nugra; Muhlas Sambodo, Irba' (Fakultas Pertanian Universitas Janabadra, 2025)
The purpose of this study was to determine the factors that influence employee work motivation at the Inti Rasa factory in Singkawang City. The variables in this study are compensation or salary, work environment, work facilities, work performance, recognition from superiors, and the work itself. The method used in this study is a descriptive qualitative method with data collection techniques through observation and questionnaires. The sample in this study was 27 people using the census sampling technique, where all members of the employee population were sampled. The analysis tool used was the Likert scale and the level of respondent perception. The results of the study on the salary variable, the average value was 3.98. For the work environment variable, the average value was 4.03. For the work facility variable, the average value was 4.16. On the work performance variable, the average value was 4.01. The recognition variable from superiors, the average value was 4.12. The work variable itself, the average value was 3.93. The total average overall was 4.04, so the influence of motivation given by the Inti Rasa Singkawang factory was categorized as high or satisfactory.